Comparison of Canal Preparation Pattern of K3 and ProTaper Rotary Files in Curved Resin Blocks - Mohammadzade Akhlaghi, Nahid; Khalilak, Zohreh; Baradaran Mohajeri, Ladan; Sheikholeslami, Mahshid; Saedi, Saeed (Iranian Endodontic Journal, 2008)
INTRODUCTION: The purpose of this study was to evaluate and compare canal preparation pattern of K3 and ProTaper rotary files in curved resin blocks. MATERIALS AND METHODS: Twenty-four resin blocks were used in this experimental study and randomly divided into two groups. Their initial images were scanned. After preparation, their images were scanned again in the same position. Pre and post preparation images were superimposed by Photoshop software and the removed resin was measured in 5 different points, and then analyzed statistically by ANOVA and T-test. RESULTS: At O point (orifice), significantly (P<0.05) more outer canal wall was removed in the ProTaper group than in the K3 group. There was no significant difference at any other points of outer wall. Removed material of inner canal wall was not significantly different between the two groups. CONCLUSION: Under the condition of this study, both systems performed acceptable preparation pattern except at the beginning of the curve.